Antiretroviral therapy alone versus antiretroviral therapy with a kick and kill approach, on measures of the HIV reservoir in participants with recent HIV infection (the RIVER trial): a phase 2, randomised trial. Issue 10227 (14th March 2020) - Fidler, Sarah; Stöhr, Wolfgang; Pace, Matt; Dorrell, Lucy; Lever, Andrew; Pett, Sarah; Kinloch-de Loes, Sabine; Fox, Julie; Clarke, Amanda; Nelson, Mark; Thornhill, John; Khan, Maryam; et al.
Summary: Background: Antiretroviral therapy (ART) cannot cure HIV infection because of a persistent reservoir of latently infected cells. Approaches that force HIV transcription from these cells, making them susceptible to killing—termed kick and kill regimens—have been explored as a strategy towards an HIV cure. RIVER is the first randomised trial to determine the effect of ART-only versus ART plus kick and kill on markers of the HIV reservoir. Methods: This phase 2, open-label, multicentre, randomised, controlled trial was undertaken at six clinical sites in the UK. Patients aged 18–60 years who were confirmed as HIV-positive within a maximum of the past 6 months and started ART within 1 month from confirmed diagnosis were randomly assigned by a computer generated randomisation list to receive ART-only (control) or ART plus the histone deacetylase inhibitor vorinostat (the kick) and replication-deficient viral vector T-cell inducing vaccines encoding conserved HIV sequences ChAdV63. HIVconsv-prime and MVA.HIVconsv-boost (the kill; ART + V + V; intervention). The primary endpoint was total HIV DNA isolated from peripheral blood CD4 + T-cells at weeks 16 and 18 after randomisation. Analysis was by intention to treat. This trial is registered with ClinicalTrials.gov, NCT02336074 . Findings: Between June 14, 2015 and Jul 11, 2017, 60 men with HIV were randomly assigned to receive either an ART-only (n=30) or an ART + V + V (n=30) regimen; all 60 participants completed the study, with no loss-to-follow-up. Mean total HIV DNA at weeks 16 and 18 after randomisation was 3·02 log10 copies HIV DNA per 10 6 CD4 + T-cells in the ART-only group versus 3·06 log10 copies HIV DNA per 10 6 CD4 + T-cells in ART + V + V group, with no statistically significant difference between the two groups (mean difference of 0·04 log10 copies HIV DNA per 10 6 CD4 + T-cells [95% CI −0·03 to 0·11; p=0·26]). There were no intervention-related serious adverse events. Interpretation: This kick and kill approach conferred no significant benefit compared with ART alone on measures of the HIV reservoir. Although this does not disprove the efficacy kick and kill strategy, for future trials enhancement of both kick and kill agents will be required. Funding: Medical Research Council (MR/L00528X/1).